Relative values or what's art worth? [accompanies the major tv series] - Buck, Louisa; Dodd, Philip (BBC Books, 1991)
Addresses such questions as: Why do we value art? Does the extraordinary price paid for certain paintings bear any relation to their artistic value? Why do we care so much about originality in art?
Keywords: Kunst; Art patronage; Art -- Collectors and collecting; Art -- Prices; Werturteil